Sistem Informasi Pengelolaan Data Inventaris Berbasis Web di SMPN 18 Medan - Triwindi Ramadana; Leni Marlina; Hendry (Jurnal Nasional Teknologi Komputer, 2026)
Inventory management is an important activity in educational institutions to ensure that facilities and infrastructure can be monitored and utilized effectively. SMP Negeri 18 Medan still manages inventory data manually using separate physical records and spreadsheet files, which leads to data redundancy, recording errors, and difficulties in searching and reporting inventory information. This study aims to develop a web-based inventory data management information system to improve the efficiency and accuracy of inventory management at SMPN 18 Medan. The research methodology used is a software development method based on the System Development Life Cycle (SDLC), which includes requirement analysis, system design, implementation, and testing. The system is developed using HTML, CSS, PHP, JavaScript, and MySQL as the database. The results show that the developed system is able to organize inventory data centrally, facilitate data search, support asset monitoring, and generate inventory reports more efficiently. The system helps reduce recording errors and supports better decision-making related to school asset management.